Sindhenan Gending Budheng-Budheng Laras Pelog Pathet Nem Kendhangan Semang Alit - Sholichah, Entin (GHURNITA: Jurnal Seni Karawitan, 2025)
This research entitled “Sindhenan Gending Budheng-Budheng Laras Pelog Pathet Nem Kendhangan Semang Alit” is one of the methods in working on lirihan music that is focused on sindhenan analysis. Budheng-Budheng is one of the many ageng gendings of Yogyakarta style that is very rarely presented among the general public. This research aims to find out the application of sindhenan in the Budheng-Budheng gending and realize it in the form of written works and works in the form of performances as one of the requirements to complete the lecture period. This research is a qualitative research using descriptive analysis method which means describing and analyzing sindhenan in Gending Budheng-Budheng Laras Pelog Pathet Nem Kendhangan Semang Alit through several gradual steps, including: artwork design, data collection and composing process. This music is a raw material that must be processed first before being presented. As for the benefits, it is a form of appreciation in documenting and developing traditional gendings, thus adding to the treasury of sindhenan in Yogyakarta style lirihan gendings.